PERAN PEMERINTAH KABUPATEN JAYAPURA DALAM PENCAPAIAN MILLENIUM DEVELOPMENT GOALS (MDGs) DI BIDANG PENDIDIKAN TAHUN 2013 - ARIA ADITYA SETIAWAN; PELIMAN NDIBAU (DINAMIS, 2014)
This study try to describe and analyze the role of Jayapura Regency Government in achieving the MDGs in Education sector in 2013, where the MDGs into a single program that had been agreed upon by all countries, including Indonesia. Millennium Development Goals (MDGs) or in Indonesian translates to the Millennium Development Goals, is a paradigm of global development, the Millennium Summit declared by the 189 member states of the United Nations (UN) in New York in September 2000. All countries present at the meeting committed to integrate the MDGs as part of the national development program in an effort to handle the settlement of issues related to the very fundamental about the fulfillment of human rights and freedoms. The Declaration is a member of the UN agreement on global development towards a package that is encapsulated in a few goals, including achieving basic education for all. In answer to these problems the writer used descriptive research data collection instruments in the form of interviews and observations. It is expected that this study may be one that can be used as a reference publication in local journals, especially scientific journals within the University and the Faculty of University of Science and Technology Fessospol Jayapura (USTJ), and also as an input to stakeholders and policy makers in the Government of Jayapura district, especially in the field of education about the implementation of the MDGs strategy.